PEMANFAATAN INSTAGRAM SEBAGAI KOMUNIKASI PROMOSI WISATA TAMAN BALEKAMBANG SURAKARTA - Rismawati; Yuliar, Ade; Yanita Senja, Puput (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
In the digital era, Instagram media users are increasingly from various social circles, for example, managers or sectors in the world of tourism such as Balekambang Park Surakarta. Balekambang Park tourism is one of the interesting places both from a historical, cultural and environmental point of view. Instagram as one of the promotional media for Balekambang Park tourism because it has a large number of followers. With the effective use of Instagram, it can make Balekambang Park a popular tourist spot. The purpose of this research is to find out the utilisation of Instagram used for promotional communication and to find out the obstacles to promotion using Instagram. In this study, researchers used a descriptive qualitative approach, namely by providing an explanation or description of the problem at hand and supported by primary and secondary data. The results of this study show that Balekambang Park utilises the features provided by Instagram as a promotional media. The use of Instagram as a promotional media is reviewed from the aspects of tourism promotion content, user aspects and economic impact. While the promotion carried out by Balekambang Park through Instagram also has several obstacles, which include obstacles in human resource management, inadequate live streaming tools, and regarding content.